The sleepwalkers - Thomas, Scarlett (Simon & Schuster, 2024)
Still reeling from the chaos of their wedding, Evelyn and Richard arrive on a tiny Greek island for their honeymoon. It's the end of the season and a storm is imminent. Determined to make the best of it, they check into the sun-soaked doors of the Villa Rosa. Already feeling insecure after seeing the "beautiful people," the seemingly endless number of young models and musicians lounging along the Mediterranean, Evelyn is wary of the hotel's owner, Isabella, who seems to only have eyes for Richard. Everyone seems to want to talk about the sleepwalkers, save for Hamza, a young Turkish man Evelyn had seen with some "beautiful people," as well as the "dapper little man"--the strange yet fashionable owner of the island's lone antiques and gift shop she sees everywhere. But what at first seemed eccentric, decorative, or simply ridiculous, becomes a living nightmare. Evelyn and Richard are separated the night of the storm and forced to face dark truths, but it's their confessions around the origins of their relationship and the years leading up to their marriage that might save them. Exhilarating, suspenseful, and also very funny, The Sleepwalkers asks urgent questions about relationships, sexuality, and the darkest elements of contemporary society--where our most terrible secrets are hidden in plain sight.--Publisher's site.